Watertight integrity of underwater robotic vehicles by self-healing mechanism - Ma, G. (Ain Shams University, 2021)
Self-healing mechanism (SHM) application has attracted interest due to ability to self-heal as response to damage situations in various conditions, and is being actively explored. However, the application of SHM that can be autonomously triggered for temporarily keeping structural integrity of underwater robotic vehicle (URV) under flooding condition is still scarce publicly. This paper describes an investigation in watertight integrity performance of URV's hull under damaged stability criteria. The main goal is to investigate the characterization of a rapid SHM through an experiment for identifying progressive flooding in a damaged URV's hull. Here, it is demonstrated that the effectiveness of sodium polyacrylate, a kind of superabsorbent polymers (SAP), had been studied by applying the polymer on an experimental model of damaged URV's hull. A comparison is studied for the stability of the flooded URV and the mass of water accumulated inside the URV's hull between the cases of before and after applying the SHM in the damaged model under different damaged conditions. The results showed that the SHM application had rapidly blocked the damaged leak hole and prevented severe water flow ingress in the damaged URV's hull. Swift recovery of buoyancy was obtained, as the volume of absorbed water by SHM was converted into equivalent buoyancy loss. These findings are establishing a fundamental knowledge for implementation of SHM in underwater robotic structures. Â© 2020